Development of problem-solving-based worksheets to improve critical thinking skills in IPAS subjects - Rahmasari Resti Khoirina; Chairul Amriyah; Rahma Diani (Inovasi Kurikulum, 2025)
Student Worksheets (Lembar Kerja Peserta Didik or LKPD) are currently being developed into innovative learning media and play a crucial role in supporting the 21st-century learning process, particularly in enhancing critical thinking skills for students. This study aims to develop problem-solving-based LKPD that can improve critical thinking skills in science in grade IV of elementary school/Islamic elementary school. The need for this LKPD is supported by the low critical thinking skills of students today, as well as the importance of active and meaningful learning to face the challenges of 21st-century education. The research method used is development research with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research sample was taken by simple random sampling from grade IV students of the elementary school/Islamic elementary school in two schools, with a pretest-posttest control group experimental design. The results of the study showed that the critical thinking scores of students who used problem-solving-based LKPD increased significantly from the average pretest and posttest scores. In contrast, students who used conventional methods only experienced a smaller increase. Based on these results, it can be concluded that the development of problem-solving-based LKPD is effective in improving students' critical thinking skills, so it is recommended for use as an innovative teaching material.   Abstrak Lembar Kerja Peserta Didik (LKPD) saat ini berkembang menjadi media pembelajaran yang inovatif dan sangat penting dalam mendukung proses pembelajaran abad 21, khususnya dalam meningkatkan keterampilan berpikir kritis. Penelitian ini bertujuan untuk mengembangkan LKPD berbasis problem solving yang dapat meningkatkan keterampilan berpikir kritis pada mata pelajaran IPAS di kelas IV SD/MI. Kebutuhan terhadap LKPD ini didukung oleh rendahnya kemampuan berpikir kritis peserta didik saat ini, serta pentingnya pembelajaran yang aktif dan bermakna untuk menghadapi tantangan pendidikan abad 21. Metode penelitian yang digunakan adalah penelitian pengembangan dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Sampel penelitian diambil secara simple random sampling dari peserta didik kelas IV SD/MI di dua sekolah, dengan desain eksperimen pretest-posttest control group. Hasil penelitian menunjukkan bahwa skor berpikir kritis peserta didik yang menggunakan LKPD berbasis problem solving meningkat secara signifikan dari nilai rata-rata pretest dan posttest, sedangkan peserta didik yang menggunakan metode konvensional hanya mengalami kenaikan lebih sedikit. Berdasarkan hasil tersebut, dapat disimpulkan bahwa pengembangan LKPD berbasis problem solving efektif dalam meningkatkan keterampilan berpikir kritis peserta didik, sehingga direkomendasikan untuk digunakan sebagai bahan ajar yang inovatif. Kata Kunci: berpikir kritis; inovasi media pembelajaran; lembar kerja peserta didik; pemecahan masalah; pengembangan media pembelajaran